Two Clusters of Fluoroquinolone and Clindamycin-Resistant Clostridium difficile PCR Ribotype 001 Strain Recognized by Capillary Electrophoresis Ribotyping and Multilocus Variable Tandem Repeat Analysis - Nyč, Otakar; Tejkalová, Renata; Kříž, Zdeněk; Růžička, Filip; Kubíček, Luboš; Matějková, Jana; Kuijper, Ed; Krůtová, Marcela (Microbial drug resistance, 2017)
AIM: To perform a retrospective analysis of the high occurrence of Clostridium difficile infection in the surgical department of a Czech tertiary care hospital and to identify weaknesses in C. difficile infection (CDI) prevention and control policies. METHODS: Clinical and epidemiological data on eleven CDI cases were collected. C. difficile isolates were characterized by capillary electrophoresis ribotyping, multilocus variable tandem repeat analysis (MLVA), gyrA gene fragment sequencing, and erm(B) fragment PCR amplification. Antibiotic susceptibility to metronidazole, vancomycin, ciprofloxacin, moxifloxacin, and clindamycin was tested. FINDINGS: Eleven CDI cases were caused by C. difficile PCR ribotype 001 strains. These strains revealed two different MLVA profiles with 11 tandem repeat differences. All isolates were susceptible to metronidazole and vancomycin and resistant to ciprofloxacin (MIC ≥32 mg/L), moxifloxacin (MIC ≥32 mg/L), and clindamycin (MIC ≥256 mg/L). All isolates revealed amino acid substitution Thr82Ile, in the GyrA and were erm(B) negative. CONCLUSION: Two fluoroquinolone and clindamycin-resistant C. difficile PCR ribotype 001 strain clusters occurred at one of the surgical departments of a tertiary care hospital. Ineffective decontamination with suboptimal concentration and time of exposure of sporicidal disinfectants may have resulted in C. difficile transmission.
Keywords: multilokusová sekvenční typizace; Clostridioides difficile; centra terciární péče; Ribotyping; exprese genu; Česká republika; Ciprofloxacin; DNA gyráza; mnohočetná bakteriální léková rezistence; retrospektivní studie; Aged; DNA Gyrase; Methyltransferases; Microbial Sensitivity Tests; Tertiary Care Centers; Clostridium Infections; Gene Expression; Vancomycin; Retrospective Studies; Multilocus Sequence Typing; senioři; Amino Acid Substitution; elektroforéza kapilární; klindamycin; ciprofloxacin; lidé; Czech Republic; DNA bakterií; ribotypizace; metronidazol; DNA, Bacterial; Drug Resistance, Multiple, Bacterial; Female; Clindamycin; Anti-Bacterial Agents; substituce aminokyselin; Male; ženské pohlaví; mikrobiální testy citlivosti; Humans; mužské pohlaví; Metronidazole; fluorochinolony; Fluoroquinolones; antibakteriální látky; Minisatellite Repeats; minisatelitní repetice; klostridiové infekce; Electrophoresis, Capillary; vankomycin; methyltransferasy